EXPLORING THE REPAIR PROCEDURES USED IN NON-LINGUISTIC SKILL TEACHING AND ASSESSING THEIR RELEVANCE FOR LANGUAGE TEACHING: THE ‘START’ PROJECT - Sarah Jackson; Keith Johnson (Indonesian JELT, 2007)
This article reports on research conducted in the Department of Linguistics and English Language at Lancaster University and supported by the Arts and Humanities Research Council of the UK. ‘START’ (Skills Training And its Relevance to Teaching) examined some of the teaching procedures and practices followed by teachers of non-linguistic skills (classical singing, table tennis and flight simulation) and identified how these procedures and practices could potentially be applied to the teaching of foreign languages. The context for the research is briefly outlined and the methodology of the study described in this article. The major part of the article discusses the findings in the key area of error correction: explicit other-repair, identifying potential trouble-sources before they occur, modelling, and developing critical thinking in students. Keywords: START, explicit other-repair, trouble-sources